2018
DOI: 10.1177/0309324718789768
|View full text |Cite
|
Sign up to set email alerts
|

Residual stress, tensile strength, and macrostructure investigations on ultrasonic assisted friction stir welding of AA 6061-T6

Abstract: In recent decades, ultrasonic vibrations are used in manufacturing processes because they can improve tool life, material performance, and quality. One of them which can be integrated with ultrasonic vibrations is friction stir welding called ultrasonic assisted friction stir welding. In previous studies, the effect of ultrasonic vibrations on the mechanical, metallurgical, and thermal properties was investigated and there is not any residual stress investigations on ultrasonic assisted friction stir welding. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…This indicates that the role of grain size in increasing the hardness is higher than the role of residual stress in decreasing the hardness. These results are in acceptable agreement with the data obtained by Alinaghian et al 60 They reported that ultrasonic vibration is of prominent significance to improve the residual stress of AA6061-T6 welded by FSW.…”
Section: Resultssupporting
confidence: 92%
“…This indicates that the role of grain size in increasing the hardness is higher than the role of residual stress in decreasing the hardness. These results are in acceptable agreement with the data obtained by Alinaghian et al 60 They reported that ultrasonic vibration is of prominent significance to improve the residual stress of AA6061-T6 welded by FSW.…”
Section: Resultssupporting
confidence: 92%
“…Thereby, when the average is computed, the effects of transverse displacements and shear stresses are canceled out and the result is the surface displacements due to release of the RS normal to the surface. 44,45 Hence, the average of the measured contours is calculated point by point. Several sources such as roughness due to the EDM cut and measurement errors cause some noise in the measured data and should be eliminated because of the significant effect on the final results.…”
Section: Methodsmentioning
confidence: 99%
“…In the last decade, many papers have been devoted to residual stress analysis in incremental forming. There are various methods for measuring residual stresses such as hole drilling [20,21], slitting [22], the contour method [23], and numerical computations [4,17,20]. Maaß et al [4] analyzed the significance of kinematic hardening effects on the state of residual stress based on numerical simulations.…”
Section: Introductionmentioning
confidence: 99%